Genetic transformation of Triticeae cereals - Summary of almost three-decade's development - Hensel, Goetz (Biotechnology advances, 2020)
Triticeae cereals are among the most important crop plants grown worldwide and being used for animal feed, food and beverages. Although breeding efforts evolved over the last ten thousand years our today's crop plants, biotechnological methods would help to speed up the process and incorporate traits impossible by conventional breeding. The main research topics were related to cover the future demand on our agricultural practices to supply sufficient food for a growing world population. Target traits are resistances against viral and fungal diseases, improvement of water and nitrogen use efficiency, to tackle plant architecture, both below and aboveground and to develop varieties that could grow on dry or salty locations. Other applications are considering accumulation of useful compounds or decreasing allergenicity. This review will summarize methods to generate the material including a section how genome engineering using gRNA/Cas (CRISPR/Cas) technology could further improve the methodology and will give an overview about recent and future applications.
Keywords: lipnicovité; Barley; transformace genetická; geneticky modifikované rostliny; Clustered Regularly Interspaced Short Palindromic Repeats; genetické inženýrství; Agrobacterium tumefaciens; Biolistic gene transfer; Transformation, Genetic; Site-directed mutagenesis; Embryogenic pollen; jedlá semena; Edible Grain; Immature embryos; Plants, Genetically Modified; Transgenic; Poaceae; Genetic Engineering; pšenice; Triticum; Wheat; sekvence CRISPR